Research on the Path of Ideological and Political Education in the Course of Circuit Fundamentals for Electronic Information Majors in Higher Vocational Education - Li, Ting; Cao, Huan (Journal of Theory and Practice of Contemporary Education, 2023)
The teaching reform of "course ideological and political education" in professional courses is a systematic project. It is necessary to not only improve students' ideological and political education, but also enable teachers to improve their political literacy. Moreover, it is necessary to reflect course ideological and political education in school enterprise cooperation. This article conducts research and exploration on the implementation path of the electronic information professional course "Curriculum Ideological and Political Education" through analysis and practice.